Disillusionment Arc pada Perubahan Karakter Paul Baumer dalam Film All Quiet on The Western Front (2022) - Wafi, Boni Hibatul; Zamroni, Muhammad; Rozi, Romdhi Fatkhur (Universitas Jember, 2025)
This study aims to identify and explain how Paul Bäumer's character transformation is constructed through the combination of Todorov's three-act structure and Weiland's Disillusionment Arc. The research employs a qualitative descriptive method with a descriptive-analytical approach. Data collection techniques include visual narrative observation, story structure analysis, and literature review to strengthen the theoretical foundation. The object of this study is the film All Quiet on the Western Front (2022), focusing on Paul Bäumer’s transformation from an idealistic young soldier to a disillusioned individual overwhelmed by the harsh realities of war. The theoretical framework integrates Todorov’s three-act narrative structure, K.M. Weiland’s Disillusionment Arc, and narrative elements from Bordwell & Thompson. The findings indicate that the combination of these narrative structures effectively identifies key moments in Paul’s emotional journey, progressively shaping his negative character arc in accordance with the Disillusionment Arc pattern.